Hydrogen production from methane under the interaction of catalytic partial oxidation, water gas shift reaction and heat recovery - Chen, Wei-Hsin; Chiu, Ting-Wei; Hung, Chen-I. (International journal of hydrogen energy, 2010)
Hydrogen production from the combination of catalytic partial oxidation of methane (CPOM) and water gas shift reaction (WGSR), viz. the two-stage reaction, in a Swiss-roll reactor is investigated numerically. Particular emphasis is placed on the interaction among the reaction of CPOM, the cooling effect due to steam injection and the excess enthalpy recovery with heat recirculation. A rhodium (Rh) catalyst bed sitting at the center of the reactor is used to trigger CPOM, and two different WGSRs, with the aids of a high-temperature (Fe–Cr-based) shift catalyst and a low-temperature (Cu–Zn-based) shift catalyst, are excited. Two important parameters, including the oxygen/methane (O/C) ratio and the steam/methane (S/C) ratio, affecting the efficiencies of methane conversion and hydrogen production are taken into account. The predictions indicate that the O/C ratio of 1.2 provides the best production of H 2 from the two-stage reaction. For a fixed O/C ratio, the H 2 yield is relatively low at a lower S/C ratio, stemming from the lower performance of WGSR, even though the cooling effect of steam is lower. On the contrary, the cooling effect becomes pronounced as the S/C ratio is high to a certain extent and the lessened CPOM leads to a lower H 2 yield. As a result, with the condition of gas hourly space velocity (GHSV) of 10,000 h −1, the optimal operation for hydrogen production in the Swiss-roll reactor is suggested at O/C = 1.2 and S/C = 4–6.